2013
DOI: 10.3748/wjg.v19.i2.249
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia is a significant prognostic factor of hepatocellular carcinoma after curative therapy

Abstract: Inadequate maintenance of blood glucose in diabetic patients is a significant risk factor for recurrence of HCC and for poor survival after curative RFA therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…Insulin resistance prior to cancer treatment was identified as an independent negative factor influencing overall survival, progression-free survival and development of treatment resistance in various cancer types [28,[77][78][79][80][81][82]. A retrospective study in 130 lymphoma patients identified high fasting blood glucose levels at diagnosis as a predictor of decreased overall-and progression-free survival [77].…”
Section: Influence Of Insulin and Glucose Levels On Therapy Efficacymentioning
confidence: 99%
“…Insulin resistance prior to cancer treatment was identified as an independent negative factor influencing overall survival, progression-free survival and development of treatment resistance in various cancer types [28,[77][78][79][80][81][82]. A retrospective study in 130 lymphoma patients identified high fasting blood glucose levels at diagnosis as a predictor of decreased overall-and progression-free survival [77].…”
Section: Influence Of Insulin and Glucose Levels On Therapy Efficacymentioning
confidence: 99%
“…Nine studies [79][80][81][82][83][84][85][86][87] assessed the association between alcohol consumption and survival in hepatocellular carcinoma patients (Supplementary table 3). Many of these studies used measures of historical heavy alcohol consumption rather than current alcohol use.…”
Section: Alcohol and Survival In Liver Cancer Patientsmentioning
confidence: 99%
“…11 Furthermore, metabolic factors, such as diabetes mellitus and hyperglycemia, were also reported to be related to recurrence after RFA. 12,13 Thus, various systemic factors, not only tumor factors but also host factors, are associated with recurrence.…”
Section: Introductionmentioning
confidence: 99%